Alpine skis categorization and on-snow performance prediction form mechanical measurments - Desbiens, A. L.; Audet, J.; Benghanem, A. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Alpine skiers are faced with too many skis to choose from during shopping. The information about the skis provided by the manufacturers is also sparse, while reviews are subject to several biases (e.g., geographical, reviewer physical characteristics and skills, preferences, fatigue) and challenges (e.g., snow types, limited testing time, reviewers agreements). This limits the reliable comparison of thousands of new skis each year. As large databases of measurements are now becoming available [1,2], it is possible to envision the automated and deterministic categorization of alpine skis, as well as the prediction of their on snow performance.